Realistyczny minimalizm w kwestii prawdy - Sierszulska, Anna (Filozofia Nauki, 2006)
The paper presents three different Fregean approaches towards the question of truth, all of which can be classified as belonging to the category of minimalistic theories, namely the identity theory of McDowell and Hornsby, the 'modest' conception of truth proposed by Wolfgang Künne and the 'alethic realism' of William Alston. The conceptions are described as realistically biased, in spite of their refusal to accept 'objectual' facts as entities in the world. It is argued that a legitimate position can be distinguished within the current truth-theoretical investigations that can be called 'realistic minimalism about truth'. It is emphasised that the conceptions of meaning which are assumed by Fregean truth theories have an essential impact upon the tendency of such minimalistic theories to gravitate either towards deflationism or towards realism. Four typical characteristics of realistically biased minimalistic theories of truth are distinguished, three of which are also accepted by deflationists of different kinds. These characterisctis are: (1) assuming indefinability of truth, (2) describing truth in terms of identity between the content of a proposition and the fact, (3) accepting the status of truth as a property (the status of truth as a property is questionable for most minimalists, but there are some who accept it), and (4) describing truth as a relational property of propositions with respect to "the ways things are" in reality. Accepting the latter thesis without rejecting the first two must be grounded in assuming a referential conception of meaning, i.e. a conception of meaning according to which separate expressions and the content of a proposition as a whole concern something that is independent of the subject and of the language. Such a semantic base makes it possible for a theory of truth to be minimalistic, in the sense of not trying to define the nature of truth, while remaining realistic with respect to the question of truth. This can only be the case because the assumed referential conception of meaning itself makes the claim that the contents of true propositions express the ways things are in reality.